DEVELOPMENT OF ARCS-BASED LEARNING TOOLS CONTAINING HOTS QUESTIONS TO IMPROVE THE CRITICAL THINKING ABILITY OF CLASS VIII SMP/MTS STUDENTS - Fauziah Putri Putri; Yerizon Yerizon; I Made Arnawa; Syafriandi Syafriandi (Universitas Negeri Makassar, 2023)
The literature study and preliminary analysis conducted showed that students' critical thinking skills were still low. This study aims to determine the characteristics of Attention, Relevance, Confidence, Satisfaction (ARCS)-based learning tools that contain valid, practical, and effective HOTS questions to improve the critical thinking skills of class VIII students of SMP N 6 Padang Panjang. This research is a development research using the Plomp model. The learning tools developed are in the form of Learning Implementation Plans (RPP) and Student Activity Sheets (LKPD). The research subjects were students of class VIII SMP N 6 Padang Panjang. Data was collected through documentation, observation, interviews, questionnaires, and tests of critical thinking skills. RPP Validity Score: 3.28 and LKPD: 3.21 with a valid category. Practicality of RPP: 92.08% and LKPD: 87.35% with very practical category. The effectiveness of learning tools based on testing the average critical thinking skills of the experimental class was 81.93, control class was 76.63. Based on statistical tests, a significance value of 0.048 <0.05 was obtained, and based on the list of t distribution tables with (????????)=60 and a=0.05, 1.671. Because t_count= 2.108>1.671=t_(table) then H0 is rejected and accepts H1. Based on the test results, it can be concluded that the ARCS-based learning tools contain HOTS questions that meet valid, practical, and effective criteria to improve students' mathematical thinking skills.